Reading techniques: skimming and scanning through a class system to strengthen reading comprehension skills in the english language - Vélez Encalada, Britany Yamileth; Jurado Zambrano, Melany Gabriela (Machala: Universidad Técnica de Machala, 2024)
This study explores the application of skimming and scanning techniques to enhance reading comprehension skills in students of 3rd year of baccalaureate at Unidad Educativa 9 de octubre. The research focuses on the implementation of a class system designed to improve students' abilities to quickly identify the main ideas skimming and locate specific information (scanning) within texts. By integrating these techniques into the curriculum, the study aims to address the common challenges students face in reading comprehension, which often hinder their overall language proficiency. The methodology involved a series of structured classes progressively increasing in complexity, beginning with introductory activities to activate prior knowledge and followed by practical exercises. The effectiveness of the system was measured through pre- and post-tests, classroom observations, and student feedback. Results indicate a significant improvement in students' reading comprehension, with enhanced ability to efficiently process and understand texts. The findings suggest that the strategic use of skimming and scanning can be a valuable addition to the teaching methods employed in English language education, offering a practical approach to overcoming reading difficulties. This study contributes to the pedagogical field by providing a replicable model for educators aiming to develop critical reading skills in their students, ultimately fostering a deeper engagement with the English language.
Este estudio explora la aplicación de técnicas de skimming y escaneo para mejorar las habilidades de comprensión lectora en estudiantes de 3er año de bachillerato de la Unidad Educativa 9 de octubre. La investigación se centra en la implementación de un sistema de clases diseñado para mejorar las habilidades de los estudiantes para identificar rápidamente las ideas principales skimming y localizar información específica scanning dentro de los textos. Al integrar estas técnicas en el plan de estudios, el estudio pretende abordar los desafíos comunes que enfrentan los estudiantes en la comprensión lectora, que a menudo obstaculizan su dominio general del idioma. La metodología implicó una serie de clases estructuradas de progresiva complejidad, comenzando con actividades introductorias para activar conocimientos previos y seguidas de ejercicios prácticos. La eficacia del sistema se midió mediante pruebas previas y posteriores, observaciones en el aula y comentarios de los estudiantes. Los resultados indican una mejora significativa en la comprensión lectora de los estudiantes, con una mayor capacidad para procesar y comprender textos de manera eficiente. Los hallazgos sugieren que el uso estratégico de hojear y escanear puede ser una valiosa adición a los métodos de enseñanza empleados en la educación del idioma inglés, ofreciendo un enfoque práctico para superar las dificultades de lectura. Este estudio contribuye al campo pedagógico al proporcionar un modelo replicable para los educadores que buscan desarrollar habilidades de lectura crítica en sus estudiantes, fomentando en última instancia un compromiso más profundo con el idioma inglés.
Keywords: SKIMMING; SCANNING; READING COMPREHENSION; TEACHING-LEARNING